2002
DOI: 10.2320/matertrans.43.2711
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of MgNi by Perylene

Abstract: Amorphous MgNi was modified by ball milling with perylene and its effects on the charge/discharge capacity were examined by using a conventional two-electrode cell. It was found that both the ball milling time and perylene/MgNi ratio had great influence on the discharge capacity and cycle life of MgNi. Three types of effects were identified, depending on ball-milling conditions. One of them was the increase in the discharge capacity at the first cycle, the second type was the deceleration of the degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Ball-milling of MgNi with graphite for a short time [11][12][13] and vacuum deposition of carbon on MgNi [14] increased the discharge capacity and the cycle life of MgNi. The present authors found that ball-milling some aromatic compounds, such as benzene (C 6 H 6 ) and perylene (C 20 H 12 ) with MgNi improved the discharge capacity and/or the cycle life of MgNi [15]. Other studies reported that composition modification, such as alloying Ti [6,12,16,17], V [12,17,18], Zr, Al [16], and Y [19] with MgNi, resulted in a certain extent of improvement on the electrochemical properties of MgNi.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Ball-milling of MgNi with graphite for a short time [11][12][13] and vacuum deposition of carbon on MgNi [14] increased the discharge capacity and the cycle life of MgNi. The present authors found that ball-milling some aromatic compounds, such as benzene (C 6 H 6 ) and perylene (C 20 H 12 ) with MgNi improved the discharge capacity and/or the cycle life of MgNi [15]. Other studies reported that composition modification, such as alloying Ti [6,12,16,17], V [12,17,18], Zr, Al [16], and Y [19] with MgNi, resulted in a certain extent of improvement on the electrochemical properties of MgNi.…”
Section: Introductionmentioning
confidence: 80%
“…This transformation is considered to be very crucial for the properties of MgNi electrode. In our previous studies [8][9][10]14,15], it has been concluded that, (1) the discharge capacity of MgNi at the first cycle is determined by the amount of hydrogen absorbed during the charge process, and (2) the cycle life of MgNi could be increased if the formation of Mg(OH) 2 is suppressed. In the case of this study, Pd might affect the properties of MgNi in three possible aspects: (1) Pd itself, irrespective of crystalline or amorphous state, can absorb and desorb hydrogen during charge/discharge cycles, (2) Pd-atoms, distributing on the surface of MgNi powder, act as catalyst to improve the electron-transfer or hydrogen absorption, and (3) Pd-atoms in MgNi structure or on the surface prevent the formation of Mg(OH) 2 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ball-milling of MgNi with graphite for a short time [5][6][7] and vacuum deposition of carbon on MgNi [8] increased the discharge capacity and the cycle life of MgNi. The present authors also found that ball-milling of MgNi with some aromatic compounds, such as benzene (C 6 H 6 ) and perylene (C 20 H 12 ), improved the discharge capacity and/or the cycle life of MgNi [9]. These results suggest that the electrochemical properties, especially the cycle life of MgNi, could be improved if the formation of Mg(OH) 2 is inhibited by some kinds of modification.…”
Section: Introductionmentioning
confidence: 58%
“…For (MgNi) 90 Pd 10 , on the other hand, the discharge capacity was about 250 mAh g −1 (about 60-65% of the first cycle) even after 30 cycles. In our previous studies [2][3][4]8,9], it has been concluded that (1) the discharge capacity of MgNi at the first cycle is determined by the amount of hydrogen absorbed during the charge process and (2) the cycle life of MgNi should be increased if the formation of Mg(OH) 2 is suppressed. In the case of the present study, the discharge capacity of (MgNi) 90 Pd 10 at the first cycle was comparable with that of unmodified MgNi; namely the amount of hydrogen absorbed was not improved by the Pd addition.…”
Section: Resultsmentioning
confidence: 99%